Liver Cell Death: Update on Apoptosis. (1st August 2003) - Bilodeau, Marc
Abstract : Hepatocyte cell death is a cardinal feature of almost every liver disease. Apoptosis is a mode of cell death characterized by specific morphological and biochemical features. Over the past decade, the importance of apoptosis has been appreciated, and it is now thought to be the main mode of cell death in liver diseases. The recognition that apoptosis can be modulated by the cell itself or by the extracellular environment has given hope that treatments can be designed to modify the evolution of disease. This article presents an overview of this important phenomenon, as well as models of hepatocyte apoptosis and goals of current research. The significance of apoptosis to the pathophysiology of liver disease is discussed.